AN ANALYSIS SLANG LANGUAGE FOUND IN KELUARGA BESAR GROUP WHATSAPP - Yohanes D.P.L Benany (JURNAL ILMIAH BAHASA DAN SASTRA, 2019)
This study was conducted to examine the types of slang words and the meaning of slang language used by members of Keluarga Besar group whatsapp. This research includes morphology and phonology. To find out types of slang in terms of phonology, Chrystal (1992) was employed to analyze the data. The researcher also used theory from Harimurti Kridaksana (1989) to analysis the tetun slang language in terms of morphology. From the analysis 17th September until 17th November 2019 used the theory from crystal (1992), it was found that from four types of slang languages in terms of phonology, there are three kinds of slang languages applied by the members of Keluarga Besar group whatsapp. 115 times of occurrence was found in their conversations, divided into: addition (15), replacement (2), sound transposition divided as: word reversal (80), PVB (14), insert one letter (2), sound change (2). While for morphology process,it was found that from four types of slang words in terms of morphology, there are two kinds of slang language applied by the members of Keluarga Besar group whatsapp. 13 times of occurrence was found in their conversations divided into: prefix (11), infix (1), and reduplication (2).